Zero-fluoroscopy catheter ablation of focal atrial tachycardia from the noncoronary cusp - Skonieczny, Bartosz; Stec, Sebastian; Miszalski-Jamka, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 40-year-old nonpregnant woman with symptomatic focal atrial tachycardia (FAT) (Figure 1 A) refractory to medical therapy and with no other chronic conditions was referred for catheter ablation. Cardiac magnetic resonance (CMR) showed slightly enlarged atria with no other anomalies within the heart and aortic root (AR). On 24-hour Holter monitoring over 16 000 supraventricular ectopic beats, including 252 FAT episodes, were recorded.